1988
DOI: 10.1164/ajrccm/137.6.1364
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor Causes Increased Pulmonary Permeability and Edema: Comparison to Septic Acute Lung Injury

Abstract: Tumor necrosis factor alpha (TNF), a monokine produced by mononuclear cells in response to bacterial endotoxin (LPS), creates a syndrome similar to septic shock in animal models. To study whether TNF could induce acute lung injury similar to that seen in gram-negative sepsis, we injected recombinant human TNF (rHuTNF alpha) into guinea pigs and monitored arterial blood gases, leukocyte counts, and left atrial (Pla), pulmonary artery (Ppa), and mean arterial pressures (MAP) serially for 8 h. Pulmonary histopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
107
0
8

Year Published

1991
1991
2005
2005

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 322 publications
(117 citation statements)
references
References 18 publications
2
107
0
8
Order By: Relevance
“…This cytokine upregulates endothelial cell adhesion molecules which are required for leucocyte emigration [23], and further activates neutrophils and macrophages for enhanced superoxide radical generation as well as enhanced chemotaxis, phagocytosis and degranulation [20±22]. Furthermore, TNF-á directly increases lung vascular permeability [24] and may promote release of other cytokines and mediators, such as platelet-activating factor, leukotrienes, or nitric oxide [15]. Finally, TNF-á has a potent bronchoconstrictor effect and this may be of particular signi®cance in the PRCV-LPS model.…”
Section: Discussionmentioning
confidence: 99%
“…This cytokine upregulates endothelial cell adhesion molecules which are required for leucocyte emigration [23], and further activates neutrophils and macrophages for enhanced superoxide radical generation as well as enhanced chemotaxis, phagocytosis and degranulation [20±22]. Furthermore, TNF-á directly increases lung vascular permeability [24] and may promote release of other cytokines and mediators, such as platelet-activating factor, leukotrienes, or nitric oxide [15]. Finally, TNF-á has a potent bronchoconstrictor effect and this may be of particular signi®cance in the PRCV-LPS model.…”
Section: Discussionmentioning
confidence: 99%
“…These cytokines act synergistically on the stimulation of polymorphonuclear neutrophilic granulocyte migration [31], and stimulate vascular endothelial cells to promote transendothelial passage of neutrophils, albumin, and fluid in vitro and in animal experiments [32][33][34]. TNF-α, IL-1 and LPS induce the expression of the adhesion molecules intercellular adhesion molecule-1 (ICAM-1), vascular cell adhesion molecule-1 (VCAM-1) and E-selectin on endothelial cells, promoting adhesion to granulocytes, monocytes and lymphocytes [35][36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…Porcine pleuropneumonia is characterized by an intensive inflammation with infiltration of phagocytic cells such as neutrophils and alveolar macrophages, which are the main cells found in affected lungs (17). Previous in vivo studies have shown that A. pleuropneumoniae infection is associated with the production of a large amount of inflammatory mediators (18,19) and proinflammatory cytokines such as IL1, TNF-␣, IL8, and IL6 (20,21) that could be responsible, at least in part, for the lung injuries and tissue destruction observed in porcine pleuropneumonia (20,22). LPS are known as mediators of inflammation (16) as they interact with immune cells and activate the production of inflammatory cytokines (23,24) by these cells.…”
mentioning
confidence: 99%